Is the Indian Stock Market Efficiently Inefficient? An Empirical Investigation - Ashraf, Shahid; Baig, Mirza Allim (Indian Journal of Finance, 2019)
The present study examined the efficiency of the Indian stock market following event study methodology considering the Union Budget as an event. The daily data of selected 36 companies of different sectors over the period from 2000-2016 were considered for the analysis. We estimated standard capital asset pricing model for each company for : (a) the entire period, (b) each of the financial years, (c) 30 trading-days before announcement of the budgets, and (d) 30 trading-days after the announcement of the budgets. We found that Î²s of different companies varied over different time periods. The estimation of average excess return and cumulative average excess return of 30 trading days before and after the budgets over 16 years showed that the Indian stock market was informationally efficient in a semi-strong form. The short-term under-reaction/over-reaction represented by average excess return around the event period provided opportunities to earn abnormal profits and validated Shiller’s argument. The cumulative average excess return converging to zero over the 30 trading days before and after the budgets also lent support to Fama’s efficient market hypothesis. The study found that the budget is an important event for the Indian stock market, at least in the short time period. It is not necessarily required to trade/ invest in high Î² stocks; rather, some trading/investment strategies may be formulated to earn excess returns, particularly around the event. The arguments on market efficiency of both the schools of "efficiently inefficient".